Analysis Of The Effect Of The Inlet Air Channel (Burner) On Used Cooking Oil And Used Oil Stoves: Analisa Pengaruh Saluran Udara Masuk (Burner) Terhadap Temperatur Pembakaran Pada Kompor Berbahan Minyak Jelantah Dan Oli Bekas - Pratama, Refandi Anwar; Iswanto, Iswanto Iswanto (MEKANIKA: Jurnal Teknik Mesin, 2025)
In the period 2015 to 2020, Indonesia experienced an increase in the consumption of used cooking oil and used oil by 2.32% per year, along with consumptive lifestyles and the sustainability of culinary culture. These used cooking oils can generate harmful free radicals that have the potential to cause health problems such as cancer and neurological disorders. The utilization of used cooking oil and used oil as alternative fuels can reduce waste and environmental impacts, but these uses are still limited and less efficient. This research method evaluates the stove fueled by used cooking oil and used oil with burner variations to determine its effect on flame temperature. The results showed that the maximum combustion temperature of used cooking oil reached 531.62°C at a burner hole variation of 20, while used oil had different temperature ranges between 518.37°C at a burner hole of 22, 533.16°C at a burner hole of 22, 541.55°C at a burner hole of 16. The use of appropriate technology and fuel purification is needed to increase efficiency and reduce negative impacts on the environment.